Development of a flipbook-based e-module using case study method in applied physics for civil engineering at Politeknik Negeri Nunukan - Rahmawati, Lusy; Anggini, Canda Putri; Syarifudin, Syarifudin; Anandita, Aulia Silvina; Utami, Vina Bekti (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study aims to develop and assess the feasibility of a flipbook-based e-module using the case study method for the Applied Physics course in the Civil Engineering for Urban Infrastructure Study Program at Politeknik Negeri Nunukan. The motivation behind this development stems from the absence of structured and contextual learning materials aligned with the 7th Main Performance Indicator (IKU 7), which emphasizes collaborative and participatory learning through project or case-based approaches. The research employed a Research and Development (R&D) approach using the 4D model Define, Design, Develop, and Disseminate although this study was limited to the Develop stage. Validation was carried out by material and media experts, while student feedback was gathered from a limited trial involving 22 first-semester students. The results of expert validation yielded an average score of 3.63 (91%), and student responses showed a mean score of 3.50 (88%), both categorized as "very feasible." Suggestions from experts led to several revisions, such as the addition of construction-related illustrations, real-world physics applications, glossaries, and enhancements in visual presentation. The e-module integrates case studies relevant to civil engineering projects, thereby enabling students to apply physics concepts in practical contexts. Furthermore, the flipbook format was found to increase interactivity and student motivation. The findings indicate that the flipbook-based e-module is a viable instructional medium that supports innovative learning strategies, enhances conceptual understanding, and aligns with institutional goals for quality education in technical fields.